MicroRNA-191 regulates endometrial cancer cell growth via TET1-mediated epigenetic modulation of APC. (26th February 2020) - Yang, Chiujung; Ota-Kurogi, Natsuki; Ikeda, Kazuhiro; Okumura, Toshiyuki; Horie-Inoue, Kuniko; Takeda, Satoru; Inoue, Satoshi
Abstract: Endometrial cancer (EC) is a common gynecological malignancy with relatively favourable prognosis, although alternative diagnostic and therapeutic options remain to be explored for advanced disease. Recent studies enabled to apply microRNAs (miRs) to clinical cancer management as promising diagnostic and therapeutic biomarkers. We here aimed to identify proliferation-associated miRNAs and characterize their functions in EC cells. Our small RNA-sequencing analysis showed that miR-191 is abundantly expressed in HEC-1A and Ishikawa EC cells along with the high expression of miR-182, which was previously characterized as an EC proliferation-related miRNA in EC. We showed that miR-191 was upregulated in EC tissues than in adjacent normal tissues and its knockdown repressed EC cell proliferation. In silico miRNA target screening identified that ten–eleven translocation 1 ( TET1 ) is one of the putative miR-191 targets. TET1 expression could be downregulated by miR-191 through the mRNA–miRNA interaction in the 3′-untranslated region of TET1 . In line with TET1 functions as a methylcytosine dioxygenase, which removes genome-wide DNA methylation marks, decreased TET1 expression resulted in hypermethylation in the promotor region of tumour suppressor adenomatous polyposis coli . Taken together, miR-191 could function as an oncogenic miRNA in EC and serve as a prospective diagnostic and therapeutic target for advanced disease.